Zastosowanie analizatora wielkości i kształtu cząstek Morphologi G3 do badań teksturalnych osadów - Szymura, Przemysław; Malinowska-Limanówka, Mirosława (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
The aim of this paper is to explain the usefulness of the Morphologi G3 analyser, made by the Malvern company, for studies of the morphology and shape of sediment particles. The main part of this paper includes detailed data about the analyser’s structure and particle measurement methodology for characterizing sediment texture. It explains the measurement procedures (Standard Operating Procedure SOP), allowing measurement standardisation and validation. It is important to emphasize the value of this methodology in the light of former methods of particle description and in line with other current interpretations of particle morphology.
Keywords: Sediments texture; Particles morphology; Microscopic tomography; Measurement standardisation and validation